2020
DOI: 10.3390/antibiotics9080516
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Colistin and Sitafloxacin Combinations against Multidrug-, Carbapenem-, and Colistin-Resistant Acinetobacter baumannii Using the Broth Microdilution Checkerboard and Time-Kill Methods

Abstract: Drug-resistant Acinetobacter baumannii (A. baumannii) infections are a critical global problem, with limited treatment choices. This study aims to determine the in vitro activities of colistin–sitafloxacin combinations against multidrug-, carbapenem- and colistin-resistant A. baumannii (MDR-AB, CRAB, CoR-AB, respectively) clinical isolates from tertiary care hospitals. We used the broth microdilution checkerboard and time-kill methods in this study. Synergy was found using both methods. The colistin–sitafloxac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
(47 reference statements)
0
14
1
Order By: Relevance
“…Currently, polymyxins (colistin and polymyxin B) and tigecycline are the last-resort antibiotics for the treatment of infection caused by CRAB isolates. Although colistin has shown well in vitro antibacterial activity against CRAB isolates with 99.4% susceptibility in this study and other reports (84.6% to 92.8% susceptibility), ( 10 , 24 26 ), clinical and PK/PD data demonstrate colistin and polymyxin B have limited clinical efficacy and combination with one or more active antimicrobial agents should be used. Several studies have demonstrated that colistin monotherapy against A. baumannii isolates is not inferior to colistin-based or meropenem combination therapy but has greater nephrotoxicity.…”
Section: Discussioncontrasting
confidence: 50%
“…Currently, polymyxins (colistin and polymyxin B) and tigecycline are the last-resort antibiotics for the treatment of infection caused by CRAB isolates. Although colistin has shown well in vitro antibacterial activity against CRAB isolates with 99.4% susceptibility in this study and other reports (84.6% to 92.8% susceptibility), ( 10 , 24 26 ), clinical and PK/PD data demonstrate colistin and polymyxin B have limited clinical efficacy and combination with one or more active antimicrobial agents should be used. Several studies have demonstrated that colistin monotherapy against A. baumannii isolates is not inferior to colistin-based or meropenem combination therapy but has greater nephrotoxicity.…”
Section: Discussioncontrasting
confidence: 50%
“…Using a cut-off minimal inhibitory concentration (MIC) of sitafloxacin ≤2 mg/L, the rate of susceptibility of CR A. baumannii to sitafloxacin was 91.4% [ 13 ]. The combination of colistin and sitafloxacin demonstrated an in vitro synergistic effect against A. baumannii in previous studies [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 75%
“…However, a reduction in mortality when using colistin combined with other agents was not clearly observed when compared with colistin alone [ 7 , 8 , 9 , 22 , 23 , 24 ]. The present study selected sitafloxacin to combine with colistin because sitafloxacin was found to be active against most isolates of CR A. baumannii , and colistin combined with sitafloxacin demonstrated an in vitro synergistic effect against CR A. baumannii [ 19 , 20 ]. However, the results of our randomized controlled study in 56 patients with CR A. baumannii infection showed the combination therapy not to be superior to monotherapy relative to 28-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Colistin-resistant Acinetobacter baumannii (CoR-AB) strains have now been detected worldwide including Thailand, primarily due to the increasing use of colistin against carbapenem-resistant A. baumannii (CRAB) 1 – 4 . The prevalence of CoR-AB was recently reported to be 14.3% in Thailand 5 and 13% in a recent global surveillance study 6 .…”
Section: Introductionmentioning
confidence: 96%